(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: In India almost 60-70% of its population is residing in rural and remote areas, where the services are yet to reach. Person with disabled face different kinds of barriers in accessing the health & rehabilitation services they require in several settings. Nursing personnel are the key person in community to deliver the various cares so that we need to train the nursing personnel for providing rehabilitative care. Aim: To assess the impact of Advanced Training Program On knowledge regarding Community Based Rehabilitation Protocol among Nursing Personnel Engaged in Community Health Services. Material &Method: Researcher will be used Quantitative research approach. Pre-Experimental design in the form of one group pretest & posttest as a research design. The study will be conducted in Satara district, Randomized sampling technique with 550 Nursing personnel engaged in community health services will be including. The collected data will be analyzed in terms of the objectives of the study using descriptive & inferential statistics. Expected Outcome: Developed & evaluated Community Based Rehabilitation Protocol and advance training program can be utilized by any one. Conclusion: To the best of our knowledge there were no any similar studies conducted On Knowledge Regarding Community Based Rehabilitation Protocol among Nursing Personnel Engaged in Community Health Services. All conclusions will be writing down after statistical analysis.